Common Indications for Referral to the Healthcare system for COVID-19 recovered patients versus Qatar Biobank study population: A descriptive analysis - Eldeeb, Marwa; Fthenou, Eleni; Elkousy, Noha; Sheikh, Nadia; Nasr, Mustafa; Afifi, Nahal; Al Thani, Asma; Frenneaux, Michael (Acta Biomedica Atenei Parmensis, 2022)
Background and Aim of the Work: Qatar Biobank (QBB) is actively acquiring data on the range of short- and long-term health impacts associated with COVID-19. This is performed through the COVID-19 biorepository National project. In this report, we describe the most common indications for the referral to Qatar’s healthcare system of COVID-19 biorepository participants in comparison with the Qatar Biobank (QBB) general population study. Methods Patients with a laboratory diagnosis of COVID-19, who were Qatar residents that could communicate in Arabic, English, Hindi and Urdu were eligible to participate in the COVID-19 biorepository project. Biological samples of Consented participants were collected on a weekly basis until recovery, and then monthly for a year. Participants were also offered a bone density scan three months after recovery and non-contrast MRI brain and whole-body scan six months after recovery. Number of participants requiring referral for medical follow up after recovery for any abnormal clinically significant findings were recorded and statistically compared to general population referred participants Results: The majority of referrals for the general population study was for osteopenia versus diabetes for the COVID-19 biorepository project Conclusion Descriptive analysis of the referral data of the COVID-19 participants and QBB general population (not previously affected by the virus) shows a clear difference between the two populations’ reasons for referrals. Diabetes for COVID 19 recovered participants versus osteopenia for general population Keywords: COVID19, Reason for Referrals, Diabetes, Qatar biobank